Being-towards the social: Mood and orientation to location-based social media, computational things and applications - Leighton Evans (New Media & Society, 2015)
Through an investigation of patterns of use of the location-based social network Foursquare derived from an extensive ethnographic survey of users, this paper focuses on the orientation of users towards location-based social media and mobile computational devices. Utilising Heidegger’s notions of mood and attunement to the world, the paper argues that the towards-which of the user, that is the mood of the user in a phenomenological sense, is critical to their experience of using location-based social media and the revealing of place that emerges from that usage. A contrast between a technological and a poetic or computational revealing of place can then be established based on the phenomenological orientation of user to device, application and world. The emphasis on orientation and attunement has implications for application design and research on user experience.